Early cidofovir administration might be associated with a lower probability of respiratory failure in treating human adenovirus pneumonia: a retrospective cohort study - Ko, J.-H. (Clin Microbiol Infect, 2020)
OBJECTIVE: To compare outcomes of early and delayed treatment with cidofovir for human adenovirus (HAdV) pneumonia. METHODS: A retrospective cohort study in Korean military hospitals was conducted between January 2012 and December 2018. Patients with potentially severe HAdV pneumonia with risk factors for respiratory failure were included and divided into early (within 7 days from symptom onset) and delayed (after 7 days from symptom onset) treatment groups. The primary outcome was respiratory failure development within 21 days after symptom onset. RESULTS: A total of 89 patients with potentially severe HAdV pneumonia were enrolled in the cohort; they included 62 early and 27 delayed treatment patients. All patients were males in their early 20s. Significantly fewer patients in the early treatment group progressed to respiratory failure (8/62, 12.9%), compared to the delayed group (18/27, 66.7%, p < 0.001). Early treatment was associated with a lower 21-day probability of respiratory failure by the Kaplan–Meier method (p < 0.001). On multivariate analysis, monocyte count, hypoxaemia, confusion, whole lung involvement, and early cidofovir treatment within 7 days from symptom onset were included, and monocyte count (HR 0.995, 95%CI 0.991–1.000, p 0.042), confusion (HR 4.964, 95%CI 1.189–20.721, p = 0.028), and early cidofovir treatment (HR 0.319, 95%CI 0.115–0.883, p = 0.028) were significantly associated with respiratory failure. CONCLUSIONS: Early administration of cidofovir was associated with a lower hazard for respiratory failure development. It is suggested that cidofovir be administered within 7 days from symptom onset to prevent respiratory failure in patients with potentially severe HAdV pneumonia.